Strategic Analysis of Xiaomi's Financial Stability in the Electronics Industry - Sarjono, Haryadi; Wilona, Anastasya; Ting, Laurencia Angelina; Rusli, Michelle Monica; Hagen, Raynard; Verrel S, Richard; Silviya, Ine (Economics, Business and Management Science Journal, 2026)
Xiaomi has emerged as a formidable competitor in the global electronics market, largely due to its strategic financial management and innovative marketing practices. This study examines how Xiaomi maintains financial stability amid intense industry competition. A qualitative research approach was employed, utilizing Bloomberg financial data to ensure accuracy and relevance. The analysis focused on key financial indicators, including gross profit, total debt, and liquidity ratios. Gross profit data highlights Xiaomi’s income trends, revealing a consistent increase over the years, except an 11.1% decline in 2022. This decline was not attributed to shortcomings in products or branding but rather to tightened international export policies affecting Chinese electronics. Despite this setback, Xiaomi significantly reduced its total debt from $335.86 billion in 2018. Furthermore, analysis of financial ratios, particularly cash ratios ranging from 0.36 to 0.93, indicates a stable liquidity position. Xiaomi's sustained financial performance is closely linked to its strategic focus on delivering high-quality, affordable products, leveraging online sales channels, executing effective marketing campaigns, investing in brand development, and building a comprehensive ecosystem of interconnected smart devices.